2015
DOI: 10.1021/jacs.5b04331
|View full text |Cite
|
Sign up to set email alerts
|

Mn(II) Binding and Subsequent Oxidation by the Multicopper Oxidase MnxG Investigated by Electron Paramagnetic Resonance Spectroscopy

Abstract: The dynamics of manganese solid formation (as MnOx) by the multicopper oxidase (MCO)-containing Mnx protein complex were examined by electron paramagnetic resonance (EPR) spectroscopy. Continuous-wave (CW) EPR spectra of samples of Mnx, prepared in atmosphere and then reacted with Mn(II) for times ranging from 7 to 600 s, indicate rapid oxidation of the substrate manganese (with two-phase pseudo-first-order kinetics modeled using rate coefficients of: k(1obs) = 0.205 ± 0.001 s(-1) and k(2obs) = 0.019 ± 0.001 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 100 publications
3
44
0
Order By: Relevance
“…Protein was purified using plasmid constructs and purification methods described previously 30 , 36 , 42 . To isolate untagged protein, the mnxDEFG construct was cloned onto a pTXB1 plasmid (kindly provided by the group of N. Blackburn, Oregon Health & Science University).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein was purified using plasmid constructs and purification methods described previously 30 , 36 , 42 . To isolate untagged protein, the mnxDEFG construct was cloned onto a pTXB1 plasmid (kindly provided by the group of N. Blackburn, Oregon Health & Science University).…”
Section: Methodsmentioning
confidence: 99%
“…The similar masses of MnxE and MnxF (both ~12 kDa) prevent accurate assignment of subunit stoichiometry unless the molecular mass can be measured at high resolution. Additionally, the many metals bound to Mnx 36 , 41 , 42 give rise to complex spectroscopic signatures 30 , 36 , 42 so it is difficult to investigate individual metal cofactors or binding sites. The enzyme’s fast turnover hinders efforts to capture early and intermediate stages of manganese oxide formation critical for understanding the mechanism of biomineralization 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies using electron paramagnetic resonance spectroscopy confirmed that the mechanism of the MnxG‐catalysed aerobic oxidation of Mn 2+ is akin to that for oxidation of organic substrates catalysed by smaller multicopper oxidases . In brief, three types of copper cofactors are needed to catalyse four sequential single‐electron oxidations of substrates coupled to the four‐electron reduction of O 2 to H 2 O ,.…”
Section: Introductionmentioning
confidence: 95%
“…( Brouwers et al, 2000 ; Ridge et al, 2007 ; Geszvain et al, 2013 ); but the best-characterized enzyme among these is the MnxGEF protein complex derived from Bacillus sp. PL-12 ( Butterfield et al, 2013 ; Tao et al, 2015 ; Butterfield and Tebo, 2017 ; Soldatova et al, 2017a , b ; Tao et al, 2017a , b ). The heterologously expressed and purified MnxGEF complex can perform the two electron oxidation of Mn(II) to Mn(IV) by funneling electrons through mononuclear Type I and trinuclear copper centers to dioxygen.…”
Section: Introductionmentioning
confidence: 99%